2021
DOI: 10.1039/d1nr01134k
|View full text |Cite
|
Sign up to set email alerts
|

A review of the microwave-assisted synthesis of carbon nanomaterials, metal oxides/hydroxides and their composites for energy storage applications

Abstract: Microwave-assisted synthesis of carbon nanomaterials, metal oxides/hydroxides and their composites for energy storage applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(36 citation statements)
references
References 319 publications
0
36
0
Order By: Relevance
“…Microwaves are nonionizing electromagnetic radiation exhibiting wavelengths between those of radio and infrared waves and frequencies ranging from 0.3 to 300 MHz. Microwaves convert electromagnetic energy into thermal energy [ 107 ]. An electromagnetic field heats material through molecular interactions, and microwaves penetrate the material to provide energy, which entails dielectric heating through a dipole rotation and resonance energy absorption.…”
Section: Microwave-assisted Synthesismentioning
confidence: 99%
“…Microwaves are nonionizing electromagnetic radiation exhibiting wavelengths between those of radio and infrared waves and frequencies ranging from 0.3 to 300 MHz. Microwaves convert electromagnetic energy into thermal energy [ 107 ]. An electromagnetic field heats material through molecular interactions, and microwaves penetrate the material to provide energy, which entails dielectric heating through a dipole rotation and resonance energy absorption.…”
Section: Microwave-assisted Synthesismentioning
confidence: 99%
“…Microwave is a cleaner and greener energy resource to drive the chemical reactions, and it has advantages in terms of extraordinary efficiency and high yield. The applications of microwave in chemical reactions are very wide, such as organic synthesis, biomass treatment, and nanomaterials. Most accelerating chemical reactions under the microwave irradiation can be explained by the microwave thermal effect. , Numerous experimental studies determine that not only the microwave thermal effect but also the microwave nonthermal effect play a decisive role in enhancing chemical reactions. Tiwari et al demonstrated the simultaneous activation of CH 4 and N 2 in a microwave catalytic reaction to produce NH 3 and C 2 products and found that the elementary reaction steps leading to NH 3 synthesis occurs due to the nonthermal effects of microwave irradiation. Silva et al verified that the combination of thermal and nonthermal effects during the microwave-assisted hydrothermal treatment provides ideal conditions for an efficient and rapid synthesis of pristine SrTiO 3 mesocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Odisha was one of the first states in the country to establish COVID-19 hospitals with ICUs in each district. Compared to other Indian states, and the state has done reasonably well in testing its populace for COVID-19 [8]. To respond to the crisis, the government of Odisha has enlisted the help of millions of women workers in various capacities, including spreading virus awareness and addressing health needs with the help of Accredited Social Health Activists (ASHA) and Auxiliary Nurse Midwives (ANM) working with Gaon Kalyan Samitis in rural areas and Mahila Arogya Samitis in urban areas [9].…”
Section: Introductionmentioning
confidence: 99%